Research methods and methodology towards knowledge creation in accounting - Lopes, I. T. (Contaduría y Administración, 2015)
Academic and scientific research embodies the purist way to achieve new knowledge through diversified methods and methodologies. It aims to describe and interpret multiple phenomena and their impact in the social and organizational developments. Based on 760 postgraduate concluded academic researches, in the scientific fields of accounting, auditing, and management control, a set of variables was identified towards an integrated overview of methods and methodology that historically fit with those scientific fields. This paper aims to evidence whether those methods and methodology depend from the scientific field under research and identify their impact to the theory construction and to the organizations’ development. Research in financial accounting tends to increase the positivist or mainstream approach while management accounting research is characterized by an integrated descriptive or interpretive approach. Furthermore, case studies are used as the way to strengthen the linkage and cooperation between higher education institutions, in particular business schools, and external organizations.